Trafficked women as empowered agents? : exploring the experiences of trafficked women from Sonagacchi, Kolkata : a thesis presented in partial fulfilment of the requirements for the Masters of International Development at Massey University, Manawatū, New Zealand - Rea, Phillipa (Massey University, 2018)
This thesis explores the freedom experiences of trafficked women from Sonagacchi, Kolkata, and argues that freedom for women trafficked into the sex trade is more complex than simply equating freedom to empowerment or exit from the sex trade. The trafficking of human beings is a major development issue, highlighted in the recently developed Sustainable Development Goals (SDG), which sets a target within SDG five, eight and sixteen to eradicate trafficking in all forms by 2030. To be able to reach this goal, a broad understanding of trafficking in needed. Research in the field of human trafficking is relatively recent with the majority of studies focusing on rescue and rehabilitation as the only means of exit from a trafficking situation. This thesis adds to the body of research on trafficking, by exploring the exit strategies of women who successfully exited a trafficking experience and seeking to understand the processes in women’s empowerment and agency. Field work took place in Sonagacchi, Kolkata the largest red-light area in India over a six-week period. A narrative inquiry method was used to hear the life stories of five women who have successfully exited their trafficking situation as well as interviews with four social workers. The findings of this study identified strategies that facilitated trafficked women’s exit from the sex trade. In addition, the processes of empowerment and agency that women experienced were explored, highlighting that individuals can experience empowerment processes and ssome degrees of agency even in exploitative environments. The idea that exit from the sex trade and empowerment equate to freedom is challenged within this study. It is recognised that freedom is contextual, personal and cultural in nature, and that in the context of the West Bengal sex trade, experiences of freedom encompassed contentment and well-being. The main implication of the findings of this research is that trafficked women experience empowerment and agency in the midst of their trafficking experience, but that experiences of freedom are more complex than the literature suggests, and women require healing and wholeness in order for freedom to be actualised.
Figure 2.1 (=Cattaneo & Goodman, 2015 Fig 1) was removed for copyright reasons.
Keywords: Human trafficking victims; India; Kolkata; Abused women; Prostitutes; Power (Social sciences); Agent (Philosophy); 440509 Women's studies (incl. girls' studies)